IL-4-C-590T locus polymorphism and susceptibility to asthma in children: a meta-analysis - Jin,Xiaosheng (2021)
Abstract Objectives The study aimed to evaluate the link between the IL-4-C590T polymorphism and asthma susceptibility in children by meta-analysis. Sources The study collected all the case-control studies found in PubMed, Embase, CNKI, Wanfang, VIP, and other databases until September 2019. Stata v. 15.0 was used to conduct meta-analysis, calculate the combined OR and its 95% CI, and then conduct subgroup analysis. Summary of the findings Seven studies were included in the study, containing 860 cases and 810 controls. Relative to the C allele, the T allele at the IL-4-C590T locus was associated with susceptibility to asthma in children (OR = 1.45, 95% CI: 1.05–2.01). The results of ethnicity subgroup analysis showed that there was statistical significance, with OR = 1.61 (95% CI: 1.01–2.57) in the Asian population. In the dominant and recessive genetic models, the overall test and the Asian population subgroup analysis were statistically significant. In the homozygous model, there was statistical significance, but no statistical significance in heterozygous model. Conclusions The IL-4-C590T polymorphism was associated with asthma susceptibility, and T allele and TT genotype may increase the risk of asthma susceptibility in children, especially in the Asian population.